Estudo da função túbulo-glomerular e inflamação renal em pacientes com leishmaniose visceral - Oliveira, Michelle Jacintha Cavalcante (2013)
Background. The aim of this study is to investigate abnormalities in glomerular and tubular function in VL patients. Methods. This is a prospective study with 16 VL patients before treatment with pentavalent antimonium, in hospital monitoring, in Fortaleza, Ceará, Brazil. Urinary concentration and acidification tests were performed after a 12h period of water and food deprivation using desmopressin and calcium chloride (CaCl2). Glomerular filtration rate (GFR) Fractional excretion of sodium (FENa), transtubular potassium gradient (TTKG) and solute free water reabsorption (TcH2O) were calculated. Microalbuminúria and proteinúria were measured. The VL group pre-treatment was compared to a group of 13 healthy volunteers (control group) and 5 VL patients were revalued after treatment. Aquaporin 2 (AQP2), renal outer medullary K+ channels (ROMK) and pendrin were quantified trough exosomes search in urine. Monocyte chemotactic protein-1 (MCP-1) and malondialdehyde (MDA) were quantified in urine. Results. Urinary concentration deficit was found in all VL patients before (100%) and 4 in 5 cases (80%) after treatment. Urinary osmolality was significantly lower in VL patients pre-treatment compared to control group (516±113 vs. 743±189 mOsm/L, p<0,001, after 12h period water deprivation and desmopressin). There was no difference after treatment revaluation. Urinary acidification deficit was found in 9 cases before (56,22%) and 2 (40%) after treatment, considering urinary pH > 5.5 after CaCl2 test. GRF was similar between the groups. Proteinuria was significantly higher in VL patients pré-treatment (250,6±375,5 vs. 83,7±49,2 mg/24h, p=0,022) and presented important regression after revaluation (268,1±259,4 vs. 113,3±50,1, p=0,043). FENa was higher in VL group when compared to control group. The search for AQP2 (128±88 vs.100±40%, p=0,41), ROMK (122±42 vs. 100±27%, p=0,34) and pendrin (105±7,5 vs. 100±13% p=0,48) were not significant. Urinary MCP-1 showed significant difference between VL patients before treatment and control group (374±359 vs. 42±29 pg/mg-Cr, p=0.002) well as urinary MDA (5.4±2.6 vs. 2.0±0.8 μmol/mL). Conclusion. VL patients present persistent urinary concentration and acidification deficit in 90 days period after treatment and present inflammation and incipient renal damage although other classical markers such as creatinine are not cha